Description of Ethical and Legal Dental Knowledge Level Among Students in Dentistry - Nadya Restu Ryendra; Erdianto Setya Wardhana; Grahita Aditya (MASHIJO : Medical Science and Hospital Journal, 2023)
Background: The practice of dentists must appropiate with the standards and ethics of the dental profession. Lack of understanding of the Kode Etik Kedokteran Gigi and lack of professional discipline have led to many cases of legal and ethical violations committed by doctors. Knowledge will affect a person's actions or practices, knowledge of dental law and ethics will influence students to act in accordance with dental ethics and law to prevent ethical and legal violations. Basically, the level of one's knowledge of professional ethics and dental law can be influenced by several factors. The aim to this study to determine the level of dental law and ethics knowledge. Method: The research was conducted by filling out questionnaires directly by the subject. The level of knowledge is classified into 3 levels, low, sufficient and high. Result: The results showed that students in the second year of preclinical, fourth year of preclinic, first year of clinic, second year of clinic, and third year of clinic had a good level of dental ethical and legal knowledge with an overall percentage in the range of 76-100%, while third year preclinical students have a sufficient level of knowledge. Conclusion: Sultan Agung Islamic University dental students have a good level of knowledge regarding the ethics and laws of dentistry.